Hacking web apps detecting and preventing web application security problems - Shema, Mike (Syngress, 2012)
How can an information security professional keep up with all of the hacks, attacks, and exploits on the Web? This book helps you to learn about the common threats and how to stop them, including HTML Injection, XSS, Cross Site Request Forgery, SQL Injection, Breaking Authentication Schemes, Logic Attacks, Web of Distrust, Browser Hacks and more.